2020
DOI: 10.3390/designs4040041
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Digital Design Approach for Metal Additive Manufacturing to Address Local Thermal Effects

Abstract: The reliability and performance qualification of additively manufactured metal parts is critical for their successful and safe use in engineering applications. In current powder-bed fusion type metal additive manufacturing processes, local thermal accumulations affect material microstructure features, overall part quality and integrity, as well as bulk mechanical behavior. To address such challenges, the investigation presented in this manuscript describes a novel digital design approach combining topology opt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 53 publications
0
4
0
Order By: Relevance
“…The regions with such local heat accumulations experience grain nucleation and growth for more extended periods, leading to different crystalline properties than the surrounding areas. This also leads to residual stresses that cause part distortions and failure sites at the structural scale [ 251 ].…”
Section: Characterization Of Additively Manufactured Implantsmentioning
confidence: 99%
“…The regions with such local heat accumulations experience grain nucleation and growth for more extended periods, leading to different crystalline properties than the surrounding areas. This also leads to residual stresses that cause part distortions and failure sites at the structural scale [ 251 ].…”
Section: Characterization Of Additively Manufactured Implantsmentioning
confidence: 99%
“…Multiphysics problems in optimisation are usually deemed to address thermal and mechanics conditions [521]. Recently, Cheng et al employed the Lattice Structure Topology Optimisation (LSTO) to design a cooling channel system [522] and Perumal et al found a technique to mitigate thermal accumulations by optimising lattice structures locally where such concentrations are more prone due to the metal AM process with a powder-bed fusion [523].…”
Section: Industrial Design Mechanical Engineering and Multiphysics mentioning
confidence: 99%
“…The integration of manufacturing constraints into TO is, therefore, crucial to turn the design proposal into a manufacturable geometry [5][6][7]. While in the early 2000s, casting processes were the focus of research [8][9][10][11][12], additive manufacturing (AM) is currently of most interest [13][14][15][16][17][18][19], as it allows the fabrication of bio-inspired [20] and numerical optimized structures [21][22][23][24] with ease. Nevertheless, even AM processes have restrictions, most prominently, the overhang-angle needed to provide temporary supports to prevent collapsing or warping, which have to be considered during TO [25,26].…”
Section: Introductionmentioning
confidence: 99%